Bulgaria Energy Environment Review - World Bank (Washington, DC, 2014)
The main purpose of the Energy and Environment Review (EER) was to develop and test a methodology to better integrate energy sector development and investment plans with Bulgaria's environmental objectives. It was undertaken at the request of the country's State Agency for Energy and Energy Resources (SAEER). The EER highlights the intrinsic trade-offs between Bulgaria's objective to ensure least-cost energy supply to the country and its concurrent objectives of being a dominant energy supplier in the region, minimizing its dependence on imported energy, and meeting its national and international environmental commitments. Achievement of these objectives is complicated by Bulgaria's heavy reliance on electricity to meet its own energy needs, the virtual absence of natural gas in the consumption mix of non-industrial consumers, and the fact that except for environmentally polluting lignite, the country does not have economical energy resources. Since the bulk of Bulgaria's electricity (about 80 percent) is generated from nuclear fuel and indigenous lignite, a disproportionate reliance on electricity would be costly, particularly as the country strives to meet the nuclear safety and environmental compliance requirements for accession to the European Union. Growing electricity exports over the last few years, however, have been good for Bulgaria, both from a financial point of view and in projecting Bulgaria as a stable and reliable source of electricity. Under these circumstances, crafting an energy supply strategy that is cost-effective, provides adequate energy security, and reinforces the national goals of economic growth and poverty alleviation will be challenging. Formulation of such a strategy could benefit from a wider debate among key stakeholders, such as energy suppliers, industrial and other consumers, policymakers, regulators, and investors. The Energy and Environment Review provides a useful analytical framework for such a debate.